Industrial Internet Platform (IIP) enabled Smart Product Lifecycle-Service System (SPLSS) for manufacturing model transformation: From an industrial practice survey. (April 2022) - Zhang, Xianyu; Ming, Xinguo; Bao, Yuguang; Liao, Xiaoqiang
Highlights: A reference model for SPLSS is proposed. Subsystems for SPLSS are proposed. Evolution path: from PSS to SPSS to SPLSS is given. A method of determination of service items for SPLSS is given. It has a certain reference value for industry and government. Abstract: Nowadays, the focus of enterprises is gradually expanding from product manufacturing system to Product service system (PSS). In the existing research, scholars mainly focus on the in-depth study of a certain method or technology, and the research on traditional PSS is relatively mature. In addition, it is a tendency that transform towards SPLSS with the characteristics of industrial internet platform (IIP) and sustainable operation theory. Based on this, this paper explores the research path from traditional product service system (PSS) to smart product service system (SPSS), and then to smart product lifecycle service system (SPLSS), which can endow the products with intelligent perception, intelligent analysis and intelligent decision-making capabilities based on Industrial Internet Platform (IIP). A reference model of IIP enabled SPLSS for industrial services based on system engineering method and theory from a very detailed practical investigation is proposed. Moreover, on the basis of this model, its three dimensional subsystems are expanded, including: supporting environment subsystem, evolution path subsystem, and added value subsystem. The study can provide a reference for the enterprise's manufacturing strategy and manufacturing path. It will promote the transformation and upgrading of enterprise manufacturing model to improve service efficiency and reduce operating costs, and then realize the value-added of products and services.